The Effect of Using H5P Interactive Media on Students' Mathematical Critical Thinking Ability - Madani, Salsabila Fitria; Sutiarso, Sugeng; Triana, Mella (Papanda Publisher, 2025)
One of the important mathematical thinking skills that students master is critical thinking skills. In fact, students' mathematical critical thinking skills in Indonesia are still relatively low. One of the factors that cause students to have low mathematical critical thinking skills is the use of less creative media. This study was conducted by analyzing the effect of using H5P interactive media on mathematical critical thinking skills. The purpose of this study was to determine the effect of using H5P Interactive Media on the mathematical critical thinking skills of students in grade IX SMP Negeri 1 Ketapang. The samples in this study were students of class IX B as the experimental class and students of class IX C as the control class. The design used was a pretest-posttest control group design. The data of this research is quantitative data obtained from a mathematical critical thinking ability test. Based on the results of hypothesis testing using a t-test with α = 0.05, it was found that the increase in mathematical critical thinking ability of students who took part in learning by using H5P interactive media was higher than the increase in mathematical critical thinking ability of students who took part in learning without using H5P interactive media. It can be concluded that the use of H5P interactive media has an effect on students' mathematical critical thinking skills.